Mistakes, Too Few to Mention? Impaired Self-conscious Emotional Processing of Errors in the Behavioral Variant of Frontotemporal Dementia - Scherling, Carole S.; Zakrzewski, Jessica; Datta, Samir; Levenson, Robert W.; Shimamura, Arthur P.; Sturm, Virginia E.; Miller, Bruce L.; Rosen, Howard J. (Frontiers in Behavioral Neuroscience, 2017)
Anosognosia, or lack of awareness of one’s deficits, is a core feature of the behavioral variant of frontotemporal dementia (bvFTD). We hypothesized that this deficit has its origins in failed emotional processing of errors. We studied autonomic and facial emotional reactivity to errors in patients with bvFTD (n=17), Alzheimer’s disease (AD, n=20) and healthy controls (HC, n=35) during performance of a timed two-alternative-choice button press task. Performance-related behavioral responses to errors were quantified using rates of error correction and post-error slowing of reaction times. Facial emotional responses were measured by monitoring facial reactivity via video and subsequently coding the type, duration and intensity of all emotional reactions. Skin conductance response (SCR) was measured via noninvasive sensors. SCR and total score for each facial emotion expression were quantified for each trial. Facial emotions were grouped into self-conscious (amusement, embarrassment) and negative (fear, sadness, anger, disgust, contempt) emotions. HCs corrected 99.4% of their errors. BvFTD patients corrected 94% (not statistically different compared with HC) and AD corrected 74.8% of their errors (p<0.05 compared with HC and bvFTD). All groups showed similar post-error slowing. Errors in HCs were associated with greater facial reactivity and SCRs compared with non-error trials, including both negative and self-conscious emotions. BvFTD patients failed to produce self-conscious emotions or an increase in SCR for errors, although they did produce negative emotional responses to a similar degree as HCs. AD showed no deficit in facial reactivity to errors. Although SCR was generally reduced in AD during error trials, they showed a preserved increase in SCR for errors relative to correct trials. These results demonstrate a specific deficit in emotional responses to errors in bvFTD, encompassing both physiological response and a specific deficit in self-conscious emotions, despite intact awareness and correction of errors. The findings provide a potential mechanism for anosognosia and possibly other behavioral abnormalities in bvFTD and highlight the importance of studying multiple channels of reactivity to errors, including performance related responses and emotional responses, in order to understand how impaired error processing could influence behavior.